2020
DOI: 10.1016/j.chembiol.2020.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Control of Endogenous and User-Defined Genetic Pathways Using Unique ecDHFR Pharmacological Chaperones

Abstract: Highlights d Identification of 17 new ecDHFR DD stabilizers, dose responses, counter screens d Dissection of minimal chemical and molecular requirements for ecDHFR DD stabilization d HeLa cell death sensitization by concomitant hDHFR inhibition and dnHSF1 stabilization d Simultaneous repression of ocular microglia and ecDHFR DD stabilization in vivo

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 13 publications
(38 citation statements)
references
References 53 publications
0
38
0
Order By: Relevance
“…While TMP is the canonical stabilizer for the ecDHFR-DD, we have found that non-antibiotic TMP derivatives ( Peng et al, 2019 ) or other compounds containing the 2,4-diaminopyrimidine (or triazine) ring with an aryl group ( Ramadurgum et al, 2020 ) can also promote ecDHFR-DD-POI abundance, and thus be used to conditionally control cellular signaling. Interestingly, the chemical space that can stabilize the ecDHFR-DD appears to be rather vast.…”
Section: Step-by-step Methods Detailsmentioning
confidence: 99%
See 4 more Smart Citations
“…While TMP is the canonical stabilizer for the ecDHFR-DD, we have found that non-antibiotic TMP derivatives ( Peng et al, 2019 ) or other compounds containing the 2,4-diaminopyrimidine (or triazine) ring with an aryl group ( Ramadurgum et al, 2020 ) can also promote ecDHFR-DD-POI abundance, and thus be used to conditionally control cellular signaling. Interestingly, the chemical space that can stabilize the ecDHFR-DD appears to be rather vast.…”
Section: Step-by-step Methods Detailsmentioning
confidence: 99%
“…Based on our work thus far, such endogenous pathways include, but are not limited to cFMS kinase inhibition, PI3Kγ/δ inhibition, P2X 3 and P2X 2/3 , ENaC, and pharmacological chaperoning of other proteins. As a starting point, one can begin using already validated compounds described in ( Ramadurgum et al, 2020 ), or they could source from the list of virtually identified compounds (Table S1 in Ramadurgum et al, 2020 ) most of which were not validated. (see Figure 6 for example stabilizers) Proceed with performing dose-response curves and downstream evaluation as described above in “ Evaluating ecDHFR-DD-POI Basal Abundance and Dynamic Range in Newly Generated Stable Cell Lines “.…”
Section: Step-by-step Methods Detailsmentioning
confidence: 99%
See 3 more Smart Citations